2021
DOI: 10.1002/pd.6025
|View full text |Cite
|
Sign up to set email alerts
|

Predictive accuracy of prenatal ultrasound findings for lower urinary tract obstruction: A systematic review and Bayesian meta‐analysis

Abstract: Background Lower urinary tract obstruction (LUTO) is a rare but critical fetal diagnosis. Different ultrasound markers have been reported with varying sensitivity and specificity. Aims The objective of this systematic review and meta‐analysis was to identify the diagnostic accuracy of ultrasound markers for LUTO. Materials and Methods We performed a systematic literature review of studies reporting on fetuses with hydronephrosis or a prenatally suspected and/or postnatally confirmed diagnosis of LUTO. Bayesian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Thus, initiation of routine third trimester screening In the present study, LUTO affected mainly male fetuses and a suspected LUTO diagnosis led to constantly high termination rates of nearly 50% during the observation period, confirming previously published data. 3,8 Pregnancies opting for termination were diagnosed earlier, suggesting the presence of more severe ultrasound findings and a poorer potential prognosis. 13,20 Even in those that did not terminate the pregnancy, the mortality rate was as high as 36% which can be ranked to the lower end of the scale according to previously reported rates of 23% up to 75 to 90%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, initiation of routine third trimester screening In the present study, LUTO affected mainly male fetuses and a suspected LUTO diagnosis led to constantly high termination rates of nearly 50% during the observation period, confirming previously published data. 3,8 Pregnancies opting for termination were diagnosed earlier, suggesting the presence of more severe ultrasound findings and a poorer potential prognosis. 13,20 Even in those that did not terminate the pregnancy, the mortality rate was as high as 36% which can be ranked to the lower end of the scale according to previously reported rates of 23% up to 75 to 90%.…”
Section: Discussionmentioning
confidence: 99%
“…Lower urinary tract obstruction (LUTO) affects 2 to 3 of every 10,000 fetuses 1 and is often associated with significant morbidity and mortality due to severe comorbidities such as pulmonary hypoplasia, renal insufficiency, and chronic kidney disease. 2 LUTO may be suspected prenatally in fetuses who exhibit the "classic" prenatal ultrasound features of megacystis, bilateral hydroureteronephrosis, oligohydramnios, and, while not entirely reliable, 3,4 the keyhole sign. 5 Due to the implications of a confirmed LUTO diagnosis on the child and family and the possibility of a poor prognosis, 6 40 to 53% of prospective parents may opt to terminate the pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review and Bayesian meta‐analysis by Keefe et al., prenatal ultrasound features of fetuses with HN were reviewed to determine which findings are most predictive of LUTO. Megacystis was the strongest predictor of a postnatal diagnosis of LUTO, while the classic “keyhole sign” was found to be a poor predictor 59 …”
Section: Etiologies and Suggested Initial Managementmentioning
confidence: 90%
“…In a systematic review and Bayesian meta- found to be a poor predictor. 59 Infants with a suspected LUTO should be delivered at a high-risk center due to the need for pediatric urology intervention shortly after birth, as well as neonatal intensive care support and early nephrology consult. Neonatal intensive care is needed for potential complications associated with oligohydramnios, such as lung hypoplasia, intrauterine growth restriction and feeding difficulties.…”
Section: Lower Urinary Tract Obstructionmentioning
confidence: 99%